Effect of temperature changes on the cercarial-shedding rate of two trematodes - Achiorno, Cecilia Luján (2016)
Since temperature is a key condition in the initiation of cercarial emergence, the objective of the work reported here was to evaluate the effect of that variable on the shedding of two morphologic and taxonomic types of cercariae. Bioassays were accordingly performed with snails naturally infected with either monostome or pleurolophocercous cercariae because those two cercarial types were found to be the most prevalent in the environment under study. The snails were placed in 6-ml circular plastic dishes with soft plastic stoppers containing 3 ml of reconstituted water and then sequentially exposed for 24 h to a 14:10-h light:dark cycle at 20, 25, or 30 °C. The data were analyzed at a significance level of p <0.05 by means of the InfoStat program. The optimum temperature for cercarial emergence was typically in the range of 25 °C and decreased significantly at 30 °C. We observed no significant difference in the number of cercariae emerging between the two morphologic types.